Letter: extending FIT from DG30 to NG12 patients. Issue 8 (20th September 2020) - Turvill, James
Abstract : LINKED CONTENT This article is linked to Nicholson et al and Farrugia et al papers. To view these articles, visit https://doi.org/10.1111/apt.15969 and https://doi.org/10.1111/apt.16068 and https://doi.org/10.1111/apt.16082